The Home and the World: Analysing Socio-Spatial Dynamics and Identity-Formation in Indian Picturebooks - Aditi Bhardwaj; Devjani Ray (IAFOR Journal of Cultural Studies)
Place identity constitutes a crucial component of children’s sense of self as they learn to locate themselves and others around them in relational social networks. Picturebooks – owing to their multimodality – can be employed to decode the meanings that the spaces inhabited by children are imbued with, and how they, in turn, shape children’s spatial experiences of the world. An exploration of the intersection of identity with the sense of place in children’s literature begets various questions – of access and attachment, belonging or a lack thereof, curtailment within and transgression of spatial boundaries, and the ways in which these negotiations shape children’s sense of self-identity. This paper locates fourteen contemporary Indian picturebooks within two arenas of conceptual enquiry – space and self-identity within childhood, and the multicultural experientiality of childhood as encompassing differences and structural inequalities – and studies the links between marginalisation and space in children’s literature. As the systematic disparities of caste, class, gender and indigeneity add a note of dissonance into a universal notion of childhood, children’s experiences of their physical surroundings become diverse and political. By coalescing Developmental and Environmental Psychology with content analysis, the paper addresses the spatial manifestations of marginalities within childhood and makes a case for identity-affirming, democratic and diverse socio-spatial representations of childhoods in multicultural children’s literature.